Literasi Kesehatan Dan Aksi Tindak Pencegahan Malaria Di Kampung Maribu, Kabupaten Jayapura - Assa, Inriyanti; Tuturop, Katarina L; Pariaribo, Konstantina M; Asmuruf, Frans Augusthinus (The Community Engagement Journal, 2024)
In 2023, malaria is the second most prevalent disease in Jayapura Regency. Prevention and control are crucial in mitigating the elevated prevalence of malaria. Consequently, it is essential to raise awareness regarding the significance of malaria prevention and control within the community. This community service aimed to improve the community's knowledge, attitudes, and practices around malaria. Malaria prevention measures had implemented as practices in this activity. This service had been conducted at Maribu Village, West Sentani District, Jayapura Regency. The outcomes of the activities indicated a favorable response from the community about the enhancement of information pertaining to malaria prevention and control.